Perlindungan Hak Asasi Manusia Bagi Korban Kekerasan Seksual di Indonesia - Luh Made Khristianti Weda Tantri (Universitas Airlangga, 2021)
Protection from all forms of sexual violence is part of human rights, namely the right to individual safety, the right to freedom and personal security, and self-protection of the honor and dignity of a person that are guaranteed by the constitution. The number of sexual violence that is increasing year after year is not proportional comparing to the low legal settlement obtained by victims of sexual violence. However, until now, there are no specific laws and regulations governing sexual violence In Indonesia. This research will discuss the protection of human rights for victims of sexual violence in Indonesia as an effort to protect human rights for the victims of sexual violence by using statute approach and conceptual approach. The results of this study conclude that laws related to sexual violence already exist but have not been able to provide comprehensive legal protection because there is no specific law on sexual violence.Keywords: Human Rights; Self Protection; Sexual Violence.Perlindungan dari segala bentuk kekerasan seksual merupakan bagian dari hak asasi manusia yaitu hak atas keselamatan individu, hak kebebasan dan keamanan pribadi, dan perlindungan diri atas kehormatan dan martabat seseorang yang dijamin oleh konstitusi. Angka kekerasan seksual yang semakin meningkat dari tahun ke tahunnya tidak sebanding dengan rendahnya penyelesaian hukum yang didapat oleh korban-korban kekerasan sekual. Namun demikian, hingga kini belum ada peraturan perundang- undangan khusus yang mengatur tentang kekerasan seksual di Indonesia. Penelitian ini akan membahas tentang perlindungan bagi korban kekerasan seksual di Indonesia sebagai upaya perlindungan hak asasi manusia dengan menggunakan pendekatan perundang-undangan dan pendekatan konseptual. Penelitian ini memperoleh kesimpulan bahwa peraturan perundang-undangan terkait kekerasan seksual sudah ada namun masih belum dapat memberikan perlindungan hukum yang komprehensif karena tidak adanya peraturan perundang-undangan khusus tentang kekerasan seksual.Kata Kunci: Asasi Manusia; Perlindungan Diri; Kekerasan Seksual.